Salivary Total Sialic Acid Levels Increase in Breast Cancer Patients: A Preliminary Study - YARAT, AYŞEN; ALTURFAN, EBRU IŞIK (BENTHAM SCIENCE PUBL LTD, 2011)
Breast cancer is the most common cancer in women living in the Western world, even though it occurs worldwide. Cancer and cancer therapy induce multiple oral complications including dental and periodontal disease. Saliva is a complex and dynamic biologic fluid, which reflects both oral and systemic changes. While saliva is an easily accessible body fluid, there has been little effort to study its value in cancer diagnosis. Sialic acids (SA), the end moieties of the carbohydrate chains, are biologically important and essential for functions of glycoconjugates that are reported to be altered in both blood and saliva of various cancer patients. Increased sialylation has been shown to be a characteristic feature in cancer tissue and blood in breast cancer patients. However, there is no data about salivary SA in breast cancer. The aim of this study was to evaluate salivary total sialic acid (TSA) levels in breast cancer patients who were under chemotheraphy. The study included 15 breast cancer patients in different stages and 10 healthy individuals as age-matched controls. Un-stimulated whole saliva was collected. Salivary total protein and SA levels were determined. Flow rate was calculated from salivary volume by the time of secretion. Salivary SA was significantly higher and total protein was lower in breast cancer patients compared to controls. It is concluded that sialylation may be increased in saliva of patients with breast cancer as the same way for cancer tissue and for blood. Increased salivary SA may therefore be useful as a non-invasive predictive marker for breast cancer patients and for the prevention and management of oral complications of cancer and cancer therapy to improve oral function and quality-of-life. The effects of different types of chemotherapies and different stages of the disease on salivary SA levels and salivary sialo-glycomic are worthy of being further investigated in breast cancer patients.
Keywords: Breast cancer; saliva; sialic acid; salivary flow rate; PERIODONTAL-DISEASE; SERUM; CHEMOTHERAPY; INFLAMMATION; ASSOCIATION; IMMUNITY; TUMORS; FORCE